To what extent could the Polish People’s Republic be considered a Polish state? The analysis of the problem in the historical context of views of Primate Wyszyński - Skibiński, Paweł (Studia Theologica Varsaviensia, 2019)
Card. Stefan Wyszyński, being both the Primate of Poland and the highest social authority, in the period of People’s Republic of Poland, independent of the communist authorities, was an important point of reference influencing public opinions and social attitudes in our country. His attitude towards the state, which was the People’s Republic of Poland, is extremely important for understanding not only his decisions at particular stages of relations between the communist state and the Church, but also allows us to better understand the specific character of the PRL as a political system, its relationship with the communist party and with the Soviet center of the communist bloc, and to what extent it represented the Polish nation as a political community. Analysis of the Primate’s attitude with regard to important political events (elections to the communist Sejm, his attitude to political breakthroughs and social events – especially social resistance against communist regime), supplemented with an analysis of the Primate’s homiletics, allows me to formulate the thesis that the Primate of the Millennium considered the PRL as a Polish state, however he regarded it as degenerated through the structures of external dependence on the USSR and the ideological domination of the communist party – PZPR. In conclusion, the People’s Republic of Poland was a Polish state that fulfilled some of the needs of the Polish nation, regarded as a fundamental political community, but it was still far from being perfect. However, the fact that – in his view – People’s Republic of Poland was actually the Polish state, was highly significant. It imposed on Catholics a moral obligation to participate in social life, in a space inaccessible to the communist party, and to undertake all efforts to prevent the threat of external military intervention of the USSR and its allies.